Impact of the COVID crisis on abnormal return M&A both on the part of acquiring companies and on the part of target companies in comparison with the non- crisis period - Smadinov, R. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2021)
During crises such as the current COVID-19 crisis, the number of mergers and acquisitions decreases, but the most profitable deals are made during the crisis. This study aims to determine whether an abnormal return rise of a company's stock occurs during a crisis. In this study, 28,402 M&A transactions were initially selected from the period from 2018 to the end of 2020. The event research method and regression analysis were used as methodologies. The results of this study showed that during crisis periods, in contrast to the non-crisis period, there is a significant increase in abnormal return both on the part of the target company and on the part of the acquiring company. Also, as a result of the regression analysis, it was found that, in addition to the crisis, the abnormal return is rather strongly influenced by the method of payment with which the buyer company will buy out the target company.